Suppression of spastin Mutant Phenotypes by Pak3 Loss Implicates a Role for Reactive Glia in AD-HSP - Ozdowski, Emily F.; Wentzell, Jill S.; Engert, Stefanie M.; Abbott, Helena; Sherwood, Nina T. (Frontiers in Neuroscience, 2020)
Neurodegenerative mechanisms due to mutations in spastin currently center on neuronal defects, primarily in microtubule and endomembrane regulation. Spastin loss in Drosophila larvae compromises neuronal microtubule distribution, alters synaptic bouton morphology, and weakens synaptic transmission at glutamatergic neuromuscular junction (NMJ) synapses. Pak3, a p21-activated kinase that promotes actin polymerization and filopodial projections, is required for these spastin mutant defects; animals lacking both genes have normal NMJs. Here we show that Pak3 is expressed in central and peripheral glial populations, and reduction of Pak3 specifically in subperineurial glial cells is sufficient to suppress the phenotypes associated with spastin loss. Subperineurial glia in the periphery ensheathe motor neuron axons and have been shown to extend actin-based projections that regulate synaptic terminals during normal NMJ development. We find that these subperineurial glial projections are Pak3-dependent and nearly twice as frequent in spastin mutants, while in Pak3, spastin double mutants, neither glial projections nor synaptic defects are observed. Spastin deficiency thus increases Pak3-dependent subperineurial glia activity, which is in turn required for neuronal defects. Our results demonstrate a central role for Pak3-mediated, altered glial behavior in the neuronal defects due to spastin loss, and suggest that a similar reactive glia-mediated mechanism may underlie human AD-HSP pathogenesis.